Teachers' Perception on Causes of Organizational Dissent - Orkun Öztürk; Osman Titrek (Sakarya University Journal of Education)
In the study, it was aimed to present the perceptions of the teachers working at public and private schools located in Adapazarı, Serdivan and Erenler districts of Sakarya on causes of organizational dissent. The target population of the research consisted of 6277 teachers. As the sample of the study, 573 teachers who were chosen via stratified sampling method participated in the study. As the data collection tool, “Causes of Dissent”, a subscale of “Organizational Dissent Scale” which was developed by Özdemir (2010), was utilized. In the data analysis, means and standard deviations of the responses to the scale items were calculated. T-test and ANOVA were utilized to demonstrate whether the teachers’ perceptions on causes of organizational dissent showed any significant difference in accordance with different variables. The results of the study indicated that there is no significant difference in the teachers’ percepions on causes of organiational dissent according to gender, age, education level, work experience, marital status, union membership, school size, and managerial experience. On the other hand, it was found out that there is a significant difference in teachers’ perceptions on causes of organizational dissent in accordance with the perceived management style of school administrators.